Strategi Employer Branding Perusahaan melalui Media Sosial Instagram @mncleasing.id: Studi Kasus pada PT MNC Guna Usaha Indonesia - Lintang Ayu Prasasti; Ike Oktaviani (IAI Nasional Laa Roiba Bogor, 2026)
Competition in attracting and retaining top talent drives companies to build their image as preferred employers. In the digital era, social media particularly Instagram—has become a primary channel in employer branding strategies. This study analyzes the employer branding strategy of PT MNC Guna Usaha Indonesia (MNC Leasing) through its official Instagram account @mncleasing.id. This research employs a qualitative descriptive approach using content analysis of the company's Instagram posts during January–June 2024. A total of 763 posts were analyzed and categorized based on themes relevant to employer branding. The findings indicate that @mncleasing.id consistently applies five employer branding content categories: work culture, company values, achievements and awards, recruitment, and service information linked to employee professionalism. Findings are analyzed using Social Identity Theory (Tajfel & Turner, 1979) and Organizational Attractiveness (Lievens & Highhouse, 2003). This study concludes that the company builds its image as a professional, innovative, and dedicated workplace through consistent messaging and visual identity on Instagram.